2009
DOI: 10.1128/jvi.02286-08
|View full text |Cite
|
Sign up to set email alerts
|

EBNA3C Can Modulate the Activities of the Transcription Factor Necdin in Association with Metastasis Suppressor Protein Nm23-H1

Abstract: Previous studies have demonstrated the interaction between the Epstein-Barr virus (EBV) nuclear antigen 3C (EBNA3C) and the metastatic suppressorEpstein-Barr virus (EBV) is a human gammaherpesvirus which predominantly targets B cells and epithelial cells and is associated with a number of human cancers, including Burkitt's lymphoma, nasopharyngeal carcinoma, Hodgkin's disease, AIDS-associated and transplant-associated immunoblastic lymphoma, and, controversially, invasive breast carcinoma (9, 61). In vitro inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 81 publications
(109 reference statements)
0
47
0
Order By: Relevance
“…Subsequent work has confirmed this interaction in lymphoblastoid cells (Murakami et al 2005). The Robertson lab developed the hypothesis that the Nm23-H1/EBNA-3C interaction regulates the latter's transcriptional activity, including the targets Cox-2 and αV integrin; these effects may be indirect, mediated through interactions with the Sp1, Necdin, and GATA transcription factors (Kaul et al 2009;Choudhuri et al 2006). EBNA-3C has been demonstrated to induce tumor cell motility in vitro and metastasis in vivo, and increased Nm23-H1 expression counters this phenotype (Murakami et al 2005;Kaul et al 2007;Subramanian et al 2001a).…”
Section: Transcriptional Regulationmentioning
confidence: 87%
“…Subsequent work has confirmed this interaction in lymphoblastoid cells (Murakami et al 2005). The Robertson lab developed the hypothesis that the Nm23-H1/EBNA-3C interaction regulates the latter's transcriptional activity, including the targets Cox-2 and αV integrin; these effects may be indirect, mediated through interactions with the Sp1, Necdin, and GATA transcription factors (Kaul et al 2009;Choudhuri et al 2006). EBNA-3C has been demonstrated to induce tumor cell motility in vitro and metastasis in vivo, and increased Nm23-H1 expression counters this phenotype (Murakami et al 2005;Kaul et al 2007;Subramanian et al 2001a).…”
Section: Transcriptional Regulationmentioning
confidence: 87%
“…Later, in our laboratory, an amino acid sequence Blast analysis of the EBNA-3C-interacting domain demonstrated a significant sequence homology to Necdin, a member of the MAGE family of proteins known to regulate multiple cellular processes, including cell cycle regulation and apoptosis [64]. The most significant structural feature of the MAGE proteins is in a large central MAGE homology domain flanked by variable amino- and carboxy-terminal domains [65].…”
Section: Ebna-3c: An Essential Ebv-encoded Multifunctional Proteinmentioning
confidence: 99%
“…The most critical biological consequences of Necdin are its negative impact on cell proliferation and its anti-angiogenic activity [65]. Necdin functions as a potent transcriptional repressor either through direct binding with DNA at guanosine clusters within the promoter region of target genes or through its interaction with other major transcription factors, including p53, E2F1 and Hif-1α [58,64,66]. It has also been reported that EBV-transformed B lymphocytes show a higher methylation status within the CpG islands of the Necdin promoter compared with primary lymphocytes [64].…”
Section: Ebna-3c: An Essential Ebv-encoded Multifunctional Proteinmentioning
confidence: 99%
“…Furthermore, EBNA3C amino acids 365-545 or 724-826 repress or activate transcription when tethered to DNA by the Gal4 DNA binding domain (27,28). Moreover, EBNA3C interacts with other transcription factors or regulators, including HDAC1, CtBP, SMN, DP103, p300, prothymosin alpha, Sin3A, NcoR, and NECDIN (29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%